2017
DOI: 10.1002/mnfr.201601112
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol suppresses lipoprotein‐associated phospholipase A2 expression by reducing oxidative stress in macrophages and animal models

Abstract: Based on our results, the protective effects of resveratrol on cardiovascular events may be related to its ability to suppress Lp-PLA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…High content atherogenic diets induce significant liver damage in both humans and laboratory animals and are responsible for fatty liver disease [140,141]. Studies have demonstrated the hepatoprotective effects of resveratrol in the high-fat dietary model of liver damage [142][143][144][145].…”
Section: Resveratrol In Liver Damage Induced By Atherogenic Dietmentioning
confidence: 99%
“…High content atherogenic diets induce significant liver damage in both humans and laboratory animals and are responsible for fatty liver disease [140,141]. Studies have demonstrated the hepatoprotective effects of resveratrol in the high-fat dietary model of liver damage [142][143][144][145].…”
Section: Resveratrol In Liver Damage Induced By Atherogenic Dietmentioning
confidence: 99%
“…A sharp rise in ROS generation leads to the opening of MPTP, resulting in the imbalance of H + on the inner membrane of mitochondria, destroys membrane proteins, inhibits ATP synthesis, and causes mitochondrial swelling, all of which may exacerbate necrotic or apoptotic cascades leading to rapid cell death [91]. Resveratrol is able to reinstate SIRT1 activation which resists against oxidative stress through the upregulation of antioxidants such as superoxide dismutase 2 (SOD2), which inhibits the mitochondrial injury by swapping out excessively generated ROS [92]. It has also been found that cyclosporine A (CsA) can inhibit MPTP constitution protein cyclophilin D to protect mitochondrial functional integrity under severe shocks [93].…”
Section: Sirt1 Helps Alleviate Oxidative Stress In Dilimentioning
confidence: 99%
“…By contrast, healthy gingival tissues did not express SIRT1 or 8-OHdG. SIRT1 inhibits oxidative stress by upregulating superoxide dismutase 2 (44), and resveratrol reduces oxidative stress in macrophages (45). Therefore, we hypothesized that SIRT1 and 8-OHdG are co-expressed in periapical granulomas as a result of oxidative stress-mediated damage to inflammatory cells, which enhances the wound healing activity of these cells.…”
Section: Discussionmentioning
confidence: 95%